2020
DOI: 10.1111/os.12684
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis between Short Stem and Conventional Femoral Stem in Patients with Osteonecrosis of Femoral Head: Metha Stem and Excia Stem

Abstract: ObjectiveTo compare the intraoperative, radiological, and clinical short‐term outcomes of cementless total hip arthroplasties (THA) using a short stem (SS) and a conventional femoral stem (CS) in a randomized prospective control study.MethodsFrom June 2011 to October 2017, patients who underwent cementless THA for idiopathic osteonecrosis of the femoral head were recruited. Patients had a minimum 2 years of follow‐up after the operation. The patients were divided into two groups: those who underwent THA using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 28 publications
1
5
0
Order By: Relevance
“…In our material, 23 procedures (12.6%) of hip arthroplasty with Metha stem were performed for sterile necrosis of the femoral bone head. Our results are similar to those of the above-mentioned studies and fully confirm the reports of other authors 32 34 .…”
Section: Discussionsupporting
confidence: 94%
“…In our material, 23 procedures (12.6%) of hip arthroplasty with Metha stem were performed for sterile necrosis of the femoral bone head. Our results are similar to those of the above-mentioned studies and fully confirm the reports of other authors 32 34 .…”
Section: Discussionsupporting
confidence: 94%
“…A recent study on the Dutch Arthroplasty Register [39] analysed 228,917 cementless conventional stems and 3,352 cementless short stems and found no significant differences in 10‐year stem revision rates (2.3% vs 3.0%), although today’s predominant short stems (Fitmore and Optimys) had lower revision rates than other less frequently used short stems (4.5%). In addition, prior clinical studies comparing conventional versus short stems found no significant differences in subsidence (0% vs 0% [19, 22]; 1% vs 0% [16]; 0% vs 2%, p = 0.554 [36]) or misalignment (0% vs 0% [19]; 2% vs 4%, p = 0.313 [36]; 1% vs 5%, p = 0.111 [13]); however, these clinical studies were underpowered to detect significant differences across groups. Based on this data, the present study performed an a priori sample size calculation to determine the number of patients that would be needed in each group to provide a significant difference in subsidence and misalignment.…”
Section: Discussionmentioning
confidence: 92%
“…In contrast, radiographic outcomes were not widely evaluated; three systematic reviews reported contradictory findings regarding bone mineral density [23, 43, 44], while one systematic review reported no significant differences in femoral offset and limb length discrepancy [12]. A number of comparative clinical studies have reported radiographic outcomes of conventional versus short stems, with cohorts varying between 25–132 per group [13, 16, 1922, 36, 37, 42], which may be underpowered to detect significant differences across groups, considering the small incidence of subsidence (0–2%) and misalignment (0–5%) [13, 16, 19, 22, 36]. In terms of subsidence, Kato et al [16] reported only one case ≥ 2 mm in the conventional group and Shin et al [36] reported only one case ≥ 2 mm in the short group, while Lacko et al [22] and Kim et al [19] reported no cases ≥ 2 mm and ≥ 3 mm respectively in either group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations